Factors influencing hepatitis B vaccination intention and behavior among college students in Tibet: Insights from the expanded theory of planned behavior - Qi Chen; Jun Ma; Ruipeng Wu; Yingting Wang; Xiaoxin Ma; Xiaolei Zheng; Hui Jin (Human Vaccines & Immunotherapeutics)
Hepatitis B (Hep B) remains a critical public health issue globally, particularly in Tibet, where vaccination rates and influencing factors among college students are yet understudied. This study applies a cross-sectional design to investigate the Hep B vaccination rate among 1,126 college students in Tibet and utilizes the expanded theory of planned behavior (ETPB) to identify vaccination behavior intention (BI) and vaccination behavior (VB). Stratified cluster sampling across three universities was used to assess behavioral attitudes (BA), subjective norms (SN), perceived behavioral control (PBC), past vaccination history (PVH) and vaccination knowledge (VK), and used structural equation modeling (SEM) for model validation and multi-group comparison. Results indicated that 16.3% of students had received the Hep B vaccine. VK notably improved BA toward vaccination (β = 0.518, p < .001). BA (β = 0.232, p < .001), PBC (β = 0.239, p < .001), SN (β = 0.385, p < .001) positively influenced BI. However, PVH failed to predict BI. BI (β = 0.448, p < .001) and PVH (β = 0.127, p < .001) were significant predictors of VB. Significant ethnic variations were noted. The positive effect of PVH on VB (β = 0.151, p < .001) and the mediating role of PBC in VB (β = 0.076, p < .05) were significant among Tibetan students. The effect of VK on BA was stronger among Tibetans (β = 0.503, p < .05),while the impact of attitude on BI was more pronounced among Han students (β = 0.366, p < .05). The vaccination rate for Hep B among college students in Tibet is relatively low, and the ETPB model effectively explains their vaccination intentions and behaviors. Tailored intervention strategies for Tibetan and Han students are recommended to boost vaccination rates effectively.